Persistent anterograde amnesia following limbic encephalitis associated with antibodies to the voltage-gated potassium channel complex. - Butler, C; Miller, T; Kaur, MS; Baker, I; Boothroyd, G; Illman, N; Rosenthal, C; Vincent, A; Buckley, C (2014)
OBJECTIVE: Limbic encephalitis (LE) associated with antibodies to the voltage-gated potassium channel complex (VGKC) is a potentially reversible cause of cognitive impairment. Despite the prominence of cognitive dysfunction in this syndrome, little is known about patients' neuropsychological profile at presentation or their long-term cognitive outcome. METHODS: We used a comprehensive neuropsychological test battery to evaluate cognitive function longitudinally in 19 patients with VGKC-LE. RESULTS: Before immunotherapy, the group had significant impairment of memory, processing speed and executive function, whereas language and perceptual organisation were intact. At follow-up, cognitive impairment was restricted to the memory domain, with processing speed and executive function having returned to the normal range. Residual memory function was predicted by the antibody titre at presentation. CONCLUSIONS: The results show that, despite broad cognitive dysfunction in the acute phase, patients with VGKC-LE often make a substantial recovery with immunotherapy but may be left with permanent anterograde amnesia.